2014
DOI: 10.1002/ajmg.b.32256
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant parietal cortex developmental trajectories in girls with turner syndrome and related visual–spatial cognitive development: A preliminary study

Abstract: Turner syndrome (TS) arises from partial or complete absence of the X-chromosome in females. Girls with TS show deficits in visual–spatial skills as well as reduced brain volume and surface area in the parietal cortex which supports these cognitive functions. Thus, measuring the developmental trajectory of the parietal cortex and the associated visual–spatial cognition in TS may provide novel insights into critical brain-behavior associations. In this longitudinal study, we acquired structural MRI data and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 52 publications
4
27
0
2
Order By: Relevance
“…The structure of the parietal lobe [1618] and its connectivity with other cortical regions (notably the frontal cortex) [19, 20] appear to differ between individuals with TS and controls. In addition, task-based [2123] and resting-state [24] functional connectivity measures between the frontal and parietal cortex are reduced in girls with TS.…”
Section: Brain Phenotype In Ts Nf1 and Ns: Clinical And Animal Modelmentioning
confidence: 99%
“…The structure of the parietal lobe [1618] and its connectivity with other cortical regions (notably the frontal cortex) [19, 20] appear to differ between individuals with TS and controls. In addition, task-based [2123] and resting-state [24] functional connectivity measures between the frontal and parietal cortex are reduced in girls with TS.…”
Section: Brain Phenotype In Ts Nf1 and Ns: Clinical And Animal Modelmentioning
confidence: 99%
“…Behavioral and brain imaging studies have reported dorsal visual stream atypicalities in TS. While a large body of research has documented atypicalities in the structure and function of posterior parietal cortex in TS (Lepage et al, 2013;Bray et al, 2013;Green et al, 2014) as well as its functionally connectivity to the frontoparietal attention network (Kesler and Reiss, 2006), accumulating evidence also suggests atypicalities to the cuneus and lingual gyrus, where V2 and V3 reside. For example, neuroimaging studies have shown that, compared with age-and sexmatched controls, both girls and adults with TS show (1) a reduction in volume of the lingual gyrus (Lepage et al, 2013), and the cuneus (Marzelli et al, 2011) and (2) reduced functional connectivity between the cuneus and the whole brain (Xie et al, 2015) as well as reduced functional connectivity within the frontoparietal network (Green et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…TS is characterized by a specific cognitive profile with relative strengths in verbal domains and weaknesses in visuospatial and executive processing (Hong et al, 2009). Compared with typically developing controls, structural imaging of the brain shows smaller gray matter volume and surface area and larger thickness of the parieto-occipital cortex in prepubertal and adolescent girls as well as adults with TS (Raznahan et al, 2010;Lepage et al, 2013;Green et al, 2014). Beyond these anatomical differences, resting-state and task-based fMRI studies find aberrant brain activity in the dorsal visual stream (Mishkin et al, 1983) of girls with TS (Kesler and Reiss, 2006;Green et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nonverbal cognition, visuo-perceptual and visuo-constructional (Green et al, 2014;Hong & Reiss, 2012) and executive skills are areas of core weakness in individuals with TS. Tactile-spatial ability has been reported as intact (Temple & Carney, 1995).…”
Section: Girls With Ts Have Normal Intelligence With An Advantage On mentioning
confidence: 99%